Proposals for settlement assyrians in brazilian paraná and british guiana 1933-1935 - Makho, Lawrence; Tawfiq, Hoger (Humanities Journal of University of Zakho, 2023)
The case of the settlement pf the Assyrians of Hakkari has preoccupied political public opinion in Iraq, Britain, and the League of Nations, which was after the events of Semele in 1933, where Britain understood in particular that it was very difficult for these Assyrians to integrate with the inhabitants of the Julamerg Valley "Hakkari", who fled from their areas of residence in 1915 for fear of oppression of the Ottoman army who attacked their areas. after the Assyrians contacted the Russians at the beginning of World War I. The significance of this study goes back to tracking those international proposals in the process of finding a home for the Assyrians, after Britain was unable to fulfill its pledges to the Assyrians, either by returning them to their areas of residence in Hakkari or establishing a nation-state for them in Kurdistan. Therefore, this study attempts to answer a number of questions, including: What is the Assyrian problem? How did this problem arise and develop? Why did Britain not fulfill its political promises to the Assyrians? Was there a promise for them to establish a nation-state like the rest of nationalities? What are the events of Semel? What is the proposal to house the Assyrians in Brazil and British Guiana? Did these proposals succeed or not? What are the obstacles to these settlement projects? This study attempts to provide answers to many other questions based on the original historical resources.